Saquinavir plus methylprednisolone ameliorates experimental acute lung injury - Zhang,Guanghua (2018)
Glucocorticoid insensitivity is an important barrier to the treatment of several inflammatory diseases, including acute lung injury (ALI). Saquinavir (SQV) is an inhibitor of the human immunodeficiency virus protease, and the therapeutic effects of SQV in ALI accompanied with glucocorticoid insensitivity have not been previously investigated. In this study, the effects of SQV on lipopolysaccharide (LPS)-mediated injury in human pulmonary microvascular endothelial cells (HPMECs), human type I alveolar epithelial cells (AT I), and alveolar macrophages were determined. In addition, the effects of SQV on an LPS-induced ALI model with or without methylprednisolone (MPS) were studied. In LPS-stimulated HPMECs, SQV treatment resulted in a decrease of high mobility group box 1 (HMGB1), phospho-NF-κB (p-NF-κB), and toll-like receptor 4 (TLR4), and an increase of VE-cadherin. Compared to MPS alone, MPS plus SQV attenuated the decrease of glucocorticoid receptor alpha (GRα) and IκBα in LPS-stimulated HPMECs. HMGB1, TLR4, and p-NF-κB expression were also lessened in LPS-stimulated alveolar macrophages with SQV treatment. In addition, SQV reduced the injury in human AT I with a decrease of HMGB1 and p-NF-κB, and with an increase of aquaporin 5 (AQP 5). SQV ameliorated the lung injury caused by LPS in rats with reductions in vascular permeability, myeloperoxidase activity (MPO) and histopathological scores, and with lowered HMGB1, TLR4, and p-NF-κB expression, but with enhanced VE-cadherin expression. By comparison, SQV plus MPS increased GRα and IκBα in lung tissues of rats with ALI. This study demonstrated that SQV prevented experimental ALI and improved glucocorticoid insensitivity by modulating the HMGB1/TLR4 pathway.